2001
DOI: 10.1038/nn763
|View full text |Cite
|
Sign up to set email alerts
|

Visual stimuli activate auditory cortex in the deaf

Abstract: Previous brain imaging studies have demonstrated responses to tactile and auditory stimuli in visual cortex of blind subjects, suggesting that removal of one sensory modality leads to neural reorganization of the remaining modalities. To investigate whether similar 'cross-modal' plasticity occurs in human auditory cortex, we used functional magnetic resonance imaging (fMRI) to measure visually evoked activity in auditory areas of both early-deafened and hearing individuals. Here we find that deaf subjects exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
362
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(407 citation statements)
references
References 13 publications
36
362
2
7
Order By: Relevance
“…Previous studies have used stimuli with different levels of linguistic content to look at plasticity in deaf individuals 2,3 . However, they have not compared language experiences, typically testing only DS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used stimuli with different levels of linguistic content to look at plasticity in deaf individuals 2,3 . However, they have not compared language experiences, typically testing only DS.…”
Section: Discussionmentioning
confidence: 99%
“…These can arise from physiological or developmental processes, or damage or insult 1 , and can be mediated by cognitive or sensory mechanisms. In congenitally deaf people, neural plasticity has been observed in the superior temporal cortex (STC) 2,3 , a region that is associated with auditory and speech sound processing. Although sensory deprivation triggers the reorganization of the cortex, the origin of the anatomical and functional changes observed in the STC of deaf individuals is not only sensory, but also cognitive, as they cannot acquire language through sound, and visual communication strategies, such as the use of sign language and speechreading, need to be developed.…”
mentioning
confidence: 99%
“…The longer the duration of auditory deprivation, the greater the over-representation of visual stimulation in hearing areas. [2][3][4] Furthermore, it has been shown that in the congenitally blind, visual cortical areas are activated during linguistic processing via touch. [5] This evidence of cortical reorganization is known as cross-modal plasticity (CMP).…”
Section: Introductionmentioning
confidence: 99%
“…De nombreuses études ont démontré qu'une plasticité similaire à celle détectée chez les aveugles existerait également chez les sourds. Il semblerait effectivement que, chez ces personnes, les régions auditives soient mobilisées afin de réaliser des tâches de nature visuelle [19][20][21]. Par ailleurs, le développement de prothè-ses auditives (implants cochléaires) permet aujourd'hui de rétablir l'audition chez les sujets sourds [22].…”
Section: La Surdité Similaire à La Cécitéunclassified